Beginning Visual Studio 2010 LightSwitch development - Nov k, Istv n (Wiley-Blackwell, 2011)
Learn how LightSwitch can accelerate and simplify application development As Microsoft's newest offering for simplifying application development, LightSwitch opens the development door to creating applications without writing code. This introductory, full-color book shows you how to quickly create, modify, and distribute information for your business with LightSwitch. Packed with simple example programs, this beginner-level resource guides you through a complete small business application using LightSwitch to demonstrate the capabilities of this exciting new tool. You'll explore the most common application development issues that developers encounter on a daily basis and learn how LightSwitch makes them easier to handle with solutions that streamline application development without requiring code. Gets you started with Visual Studio LightSwitch, Microsoft's newest offering for simplifying application development Shows you how to prepare a LightSwitch application and looks at the technologies behind a LightSwitch application Addresses working with simple data screens, working with master-detail data screens, and using exciting SQL server data Looks at deploying applications, using SharePoint 2010 lists, and extending Visual Studio LightSwitch If you're ready to simplify the application development process without writing a piece of code, then this is the book for you!